Bladder cancer. (February 2020) - Yazbek-Hanna, Marcelino; Jain, Sunjay
Abstract: Bladder cancer is the most frequently occurring tumour of the urinary tract and the eighth most common cause of cancer death in the UK. It is characterized by a high recurrence rate, pathological progression and poor survival in advanced metastatic disease. Owing to the long follow-up period and associated costs of disease monitoring, it is one of the most expensive cancers to manage. Local therapy and surveillance are the mainstays of management of early disease, which comprises 75% of cases. Radical surgery and radiotherapy are the main curative options in advanced non-metastatic disease. Chemotherapy can be used in a neoadjuvant, adjuvant or palliative setting. There remains a great need for effective tumour markers to aid diagnosis, staging, monitoring and predicting prognosis.